Екологічна політика держави у сфері публічних закупівель: підходи ЄС та законодавство України - Шевчук, Л.; Shevchuk, L. (Волин. нац. ун-т. ім. Лесі Українки, 2020)
Досліджено теоретико-правові засади екологічної політики України у сфері публічних закупівель в умовах європейської інтеграції держави. Проаналізовано екологічні стандарти ЄС та їх закріплення в національному законодавстві. Запропоноване авторське визначення поняття сучасної екологічної політики України у сфері публічних закупівель. Обґрунтовано висновок про те, що посилення екологічної складової в національному закупівельному законодавстві характеризує сучасну політику України, орієнтовану на стандарти ЄС у сфері закупівель відповідно до Директиви 2014/24 / ЄС. The article highlights the theoretical and legal principles of the environmental policy of Ukraine in the field of public procurement in the context of European integration. In the focus of the study are the EU environmental standards and their enshrinement in national legislation. The author states that the introduction of environmental norms by Law No114-IX is the result of consistent approximation of the Ukrainian legislation to the EU acquis in the field of procurement in accordance with the Association Agreement. The author argues that strengthening of the environmental component in the national procurement legislation characterizes the current policy of Ukraine, focused on EU standards in the field of procurement in terms of Directive 2014/24 / EU. But some environmental legislative regulations, provided for in the Directive 2014/24 / of EU, have not yet been properly incorporated in the national legalnormative documents on procurement. The author suggests his own definition of the concept of modern environmental policy of Ukraine in the public procurement sphere. Substantiation of the concept is based on the in-depth analysis of the legislative regulation novelties concerning ecological aspects of the procurement and findings of the researchers on the environmental issues.
Environmental Policy of the State in the Public Procurement Sphere: EU Approaches and Legislation of Ukraine
Keywords: екологічна політика; публічні закупівлі; здійснення публічних закупівель; закупівля товарів; робіт і послуг; Європейський Союз; environmental policy; public procurement; public procurement procedure; procurement of goods; works and services; European Union